2014
DOI: 10.1142/s1758825114500045
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of Defective Carbon Nanotubes Under Axial and Transverse Loads

Abstract: Elastic buckling of single walled carbon nanotubes (SWCNTs) with di-, triple- and pinhole vacancy defects under the transverse and axial compression loading is investigated based on molecular structural mechanics. In this research, the effects of length, radius, loading ratio, and the position of vacancy defect on the buckling behavior of armchair and zigzag single-walled carbon nanotubes are studied. It is found that the position of pinhole-vacancy has a significant effect on the percent of the reduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Equation (20) [42] proposes the relation between stresses and strains for outer surfaces: leftταβ±badbreak=τ0±δαβgoodbreak+()μ0±τ0±()uα,β±+uβ,α±left1embadbreak+0.16em()λ0±+τ0±uγ,γ±δαβgoodbreak+τ0±uα,β±leftτα3±badbreak=τ0±u3,α±$$\begin{eqnarray} \def\eqcellsep{&}\begin{array}{l} \tau _{\alpha \beta }^ \pm = \tau _0^ \pm {\delta _{\alpha \beta }} + \left( {\mu _0^ \pm - \tau _0^ \pm } \right)\left( {u_{\alpha ,\beta }^ \pm + u_{\beta ,\alpha }^ \pm } \right)\\[11pt] \quad +\, \left( {\lambda _0^ \pm + \tau _0^ \pm } \right)u_{\gamma ,\gamma }^ \pm {\delta _{\alpha \beta }} + \tau _0^ \pm u_{\alpha ,\beta }^ \pm \\[11pt] \tau _{\alpha 3}^ \pm = \tau _0^ \pm u_{3,\alpha }^ \pm \end{array} \end{eqnarray}$$where “+” and “−” denote the nanoplate's top and bottom surfaces, respectively. μ 0 and λ 0 represent surface layer Lamé parameters, τ 0 denotes the residual surface stress, and u,α${u_{,\alpha }}$ indicates the displacement field gradient in terms of the in‐plane directions.…”
Section: Modelling the Fluid–solid Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (20) [42] proposes the relation between stresses and strains for outer surfaces: leftταβ±badbreak=τ0±δαβgoodbreak+()μ0±τ0±()uα,β±+uβ,α±left1embadbreak+0.16em()λ0±+τ0±uγ,γ±δαβgoodbreak+τ0±uα,β±leftτα3±badbreak=τ0±u3,α±$$\begin{eqnarray} \def\eqcellsep{&}\begin{array}{l} \tau _{\alpha \beta }^ \pm = \tau _0^ \pm {\delta _{\alpha \beta }} + \left( {\mu _0^ \pm - \tau _0^ \pm } \right)\left( {u_{\alpha ,\beta }^ \pm + u_{\beta ,\alpha }^ \pm } \right)\\[11pt] \quad +\, \left( {\lambda _0^ \pm + \tau _0^ \pm } \right)u_{\gamma ,\gamma }^ \pm {\delta _{\alpha \beta }} + \tau _0^ \pm u_{\alpha ,\beta }^ \pm \\[11pt] \tau _{\alpha 3}^ \pm = \tau _0^ \pm u_{3,\alpha }^ \pm \end{array} \end{eqnarray}$$where “+” and “−” denote the nanoplate's top and bottom surfaces, respectively. μ 0 and λ 0 represent surface layer Lamé parameters, τ 0 denotes the residual surface stress, and u,α${u_{,\alpha }}$ indicates the displacement field gradient in terms of the in‐plane directions.…”
Section: Modelling the Fluid–solid Interactionmentioning
confidence: 99%
“…The influence of axial and transverse loading and length on the carrying-load capacity of carbon nanotubes (CNTs) was studied by Ziaee [42] using the molecular structural mechanics technique.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that the post-buckling deformation of the low-dimensional structures is strongly affected by the length, diameter and chirality of the nanostructures. Ziaee [2014] applied molecular structural mechanics to investigate the buckling properties of defective armchair and chiral SWCNTs under transverse and axial compression loading. He found that the position of the microscopic impurity in the structure of the low-dimensional material models plays a remarkable role on the change in the value of critical buckling force.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with extensive investigation on the mechanical properties of CNTs and CNT-polymer composites [Odegard et al, 2003;Jiang et al, 2006;Chowdhury et al, 2014;Meng et al, 2014;Rafiee et al, 2014;Ziaee, 2014;], there are relative fewer studies devoting to interpreting the electrical conductivity mechanisms and investigating how the overall electrical properties of the composites vary with their constituent features from both the theoretical and experimental perspectives [Kim et al, 2005;Gojny et al, 2006;Li et al, 2007;Yan et al, 2007;Chang et al, 2009;Seidel and Lagoudas, 2009;Takeda et al, 2011]. It should be mentioned that most studies in the literature focused on investigating the electrical properties of the as-received composites without considering the stretching effects.…”
Section: Introductionmentioning
confidence: 99%